Is there a social justice variant of South-South health cooperation?: a scoping and critical literature review - Anne-Emanuelle Birn; Carles Muntaner; Zabia Afzal; Mariajosé Aguilera (Taylor & Francis Group, 2019)
Background: In recent decades, global health scholars and policymakers have highlighted the burgeoning role of South-South cooperation (SSC) in health, claiming it constitutes a more just and even-handed approach to health cooperation. But the assertion that SSC inherently challenges power asymmetries and pursues egalitarian agendas and forms of interaction merits interrogation. Here we explore a transformative, counter-hegemonic, solidarity-oriented form of SSC - social justice-oriented South-South cooperation (SJSSC) - as differentiated from other types of health aid. Objective: The objectives of this scoping review are: 1) to determine what is known and discussed through peer-reviewed and grey literature about SJSSC in health; and 2) to identify the different features and principles of SJSSC. This review seeks to inform research agendas and identify implications for policy and practice around SJSSC. Methods: We conducted a search for relevant peer-reviewed and grey literature in eight languages and screened abstracts that met inclusion criteria. We carried out a full-text review and data extraction on included pieces and conducted a thematic analysis identifying a set of repeated themes related to the features and principles of SJSSC. Results: We identified 188 publications meeting our criteria. Through an iterative process, we developed two overarching categories: values and strategies. Each comprises four themes that allowed us to map the ideas and practices of SJSSC depicted in the literature. The values mapped are: an anti-hegemonic world view; equity-oriented and redistributive political values; egalitarian terms of cooperation; and reciprocity. The strategies encompass: solidarity-building; health justice approaches; mutual exchange and collective justice; and challenging interests of dominant classes in the health arena. Conclusion: This review rectifies ungrounded claims about SSC by identifying and mapping the research literature on SJSSC and has relevance for the conceptualization, policy development, and practice of equitable health cooperation.